Experimental Assessment of Wind Loads on Roof-to-Wall Connections for Residential Buildings - Feng, Changda; Gan Chowdhury, Arindam; Elawady, Amal; Chen, Dejiang; Azzi, Ziad; Vutukuru, Krishna Sai (Frontiers in Built Environment, 2020)
Wind hazards are one of the most disastrous events that frequently occur in the United States. Hurricane Irma, which hit the southeast coast in 2017, left a majority of damage concentrated on low-rise buildings and wooden construction in its wake. As revealed by recent hurricane damage reconnaissance, hardware-type roof-to-wall connections are especially vulnerable to high wind suction. There is only limited research on the assessment of wind loads on these roof-to-wall connections, which are important components of the wind load path. Hence, it is essential to have realistic estimates of wind effects on these connections to ensure a safe design. To fill this fundamental knowledge gap, an extensive large-scale aerodynamic testing study has been recently conducted at the NSF-Natural Hazard Engineering Research Infrastructure (NHERI) Wall of Wind (WOW) Experimental Facility (EF) to investigate wind actions resulting from simulated hurricane force winds. A wooden gable roof building of a large length scale of 1:4 was adopted for this study. Seven trusses were used to construct the roof and were connected to the top plate of the side walls. Load cells were mounted at the roof-to-wall connection (RTWC) level to measure the effective net wind-induced forces. The model was tested under different wind directions varying from 0° to 360° with an increment of 5° under varying wind speeds. In addition, three different configurations, i.e., one enclosed and two partially enclosed, were considered to assess different internal pressure scenarios that affect the net load-ing on the roof-to-wall connections and the overall roof system. The RTWC force coefficients distribution along the entire roof was obtained. The results were compared to force coefficients recommended by ASCE 7-16 version for the cases of Main Wind-Force Resisting System (MWFRS) and Component and Cladding (C&C). The experimental results were in between MWFRS and C&C values based on the ASCE provisions in general. However, for partially enclosed case, some values slightly exceeded those based on the ASCE C&C provisions. Also, the overall uplift on the roof was found to be dependent on the location of the opening (i.e., opening on long side versus short side of the building).